WRITING COMPARISON/CONTRAST PARAGRAPH WITH BLOCK STYLE - Laia, Restu Damai; Zagoto, Impiani (Universitas Nias Raya, 2024)
A comparison/contrast paragraph can be organized into two ways known point-by-point, and block model. The most of fifth semester students of English department at Nias Raya University, however, prefer to organize their writing with block model. The reasons for choosing the model were the purposes of this research. This research was carried out by using qualitative descriptive. The data were obtained through unstructured questionnaire. The result of this research showed that there are three reasons of the students in using block model in organizing the comparison/contrast paragraph; the first is easier to be organized; the next is good for the shorter paragraph; and the last is the similarities or differences between the compared subjects is understood easily. Hence, block organization for a comparison/contrast paragraph is the easiest way for the students to construct their paragraph to be interested writing rather than other style. Therefore, this information can be a consideration for the lecturer in teaching the type of the paragraph.